CerealsDB—new tools for the analysis of the wheat genome: update 2020. (4th August 2020) - Wilkinson, Paul A; Allen, Alexandra M; Tyrrell, Simon; Wingen, Luzie U; Bian, Xingdong; Winfield, Mark O; Burridge, Amanda; Shaw, Daniel S; Zaucha, Jan; Griffiths, Simon; Davey, Robert P; Edwards, Keith J; et al.
Abstract: CerealsDB (www.cerealsdb.uk.net) is an online repository of mainly hexaploid wheat ( Triticum aestivum ) single nucleotide polymorphisms (SNPs) and genotyping data. The CerealsDB website has been designed to enable wheat breeders and scientists to select the appropriate markers for research breeding tasks, such as marker-assisted selection. We report a large update of genotyping information for over 6000 wheat accessions and describe new webtools for exploring and visualizing the data. We also describe a new database of quantitative trait loci that links phenotypic traits to CerealsDB SNP markers and allelic scores for each of those markers. CerealsDB is an open-access website that hosts information on wheat SNPs considered useful for both plant breeders and research scientists. The latest CerealsDB database is available at https://www.cerealsdb.uk.net/cerealgenomics/CerealsDB/indexNEW.php.